Pertimbangan Hukum Hakim Terhadap Pelaku Tindak Pidana Korupsi - Indey, Gloria Christea Andini; Adam, Sherly; Muammar, Muammar (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2025)
Introduction: The dilemma in corruption cases, between legal certainty and substantive justice, places the judge's considerations as the main factor in ensuring a fair and effective decision. Purposes of the Research: This study aims to analyze the legal considerations of judges regarding perpetrators of corruption in decision No. 23/Pid.Sus-TPK/2024/PN Amb, as well as to analyze the imposition of sanctions on perpetratos of corruption from the perspective of the objectives of criminal punishment. Methods of the Research: The type of research used in this study is normative legal research. The approaches used are the legislative approach, the conceptual approach, and the case approach. The legal sources used are primary, secondary, and tertiary legal materials. The procedure for collecting legal materials is through literature study. The processing and analysis of legal materials use qualitative analysis. Results of the Research: The research results show that in Decision No. 23/Pid.Sus-TPK/2024/PN Amb, the panel of judges considered that although the subsidiary charges were proven, the defendant's actions were not categorized as a criminal offense because the state losses had been gradually recovered prior to the suspect's indictment, in accordance with the recommendations of the BPK's audit report through administrative mechanisms. Based on these considerations, the defendant was acquitted of all legal charges (onslag van alle rechtsvervolging) without being sentenced to any principal or additional penalties. Further research shows that the imposition of sanctions on perpetrators of corruption is not yet in line with the objectives of criminal punishment. The acquittal indicates that the acts charged were proven but did not constitute a criminal offense, so the defendant could not be punished, which means that the objective of criminal punishment to punish perpetrators of corruption was not achieved.